2019
DOI: 10.32383/appdr/112052
|View full text |Cite
|
Sign up to set email alerts
|

Quality Analysis of Semisolid Formulations With Elderflower (Sambucus Nigra L.) Liquid Extract

Abstract: The active ingredients in the liquid extract of elderflower are responsible for the antibacterial, antioxidant and anti-inflammatory effects of the plant. The main objective of the investigation was to design semisolid formulations with the elderflower extract and evaluate their quality using the biopharmaceutical research method in vitro. The quality of the elderflower (Sambucus nigra L.) extracts was evaluated spectrophotometrically by determining the total amount of polyphenols and flavonoids. The antiradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Propolis extract was obtained by maceration technique from Apis melifera honeycomb using 96% ethanol, then diluted to produce a propolis solution with a concentration of 8%. 13 Calcium hydroxide used in this research is a pro analysis Merck brand calcium hydroxide powder.…”
Section: Methodsmentioning
confidence: 99%
“…Propolis extract was obtained by maceration technique from Apis melifera honeycomb using 96% ethanol, then diluted to produce a propolis solution with a concentration of 8%. 13 Calcium hydroxide used in this research is a pro analysis Merck brand calcium hydroxide powder.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have indicated that the elderberry exhibits an antibacterial action that is found in the flowers, fruits, and leaves. Ferreira-Santos et al [ 65 ] showed that aqueous extracts of the elderflowers have an antimicrobial activity against the Gram-positive bacteria S. aureus and S. epidermidis , and Ramanauskiene et al [ 104 ] proved that ethanolic extracts had in vitro antimicrobial effects against S. aureus and B. cereus . Álvarez et al [ 105 ] investigated the antibacterial role of peptide extracts from the elderflowers against various Gram-negative bacteria ( A. salmonicida , F. psychrophilum , V. anguillarum , and V. ordalii ).…”
Section: Health Benefits and Applications Of Walnut By-products ( ...mentioning
confidence: 99%